A Dedicated Fracture Reduction Room: A Cost-Effective Alternative to the Operating Room. Issue 19 (1st October 2019) - Whitlock, Patrick W.; Little, Kevin J.; Singleton, Sandra S.; Mahmoud, Mohamed; Ngamprasertwong, Pornswan; McCarthy, James J.
Abstract : Introduction: Charges, procedural efficiency, return to activity, and complications after closed treatment of fractures performed in an operating room (OR) versus closed reduction in a dedicated fracture reduction room (FRR) were compared. Methods: Patients with closed fractures of the forearm who underwent closed reduction in the year before (OR), and after implementation of the FRR, were retrospectively reviewed. Charges, American Society of Anesthesiologists class, sex, age, length of follow-up, prior reduction, fracture location/displacement, time from injury to procedure, procedural time, time to return to activity, and complications were recorded. Results: Eighteen patients met the inclusion criteria in the FRR group (13 men, 5 women), and 22 in the OR group (18 men, 4 women). No notable differences in age, sex, follow-up, American Society of Anesthesiologists class, fracture location/displacement, incidence of prior reduction, or time to return to activity were observed. Two (9.5%) complications occurred in the FRR group versus 7 (32%) in the OR group, P > 0.05. No anesthesia complications were present. Patients treated in the FRR incurred charges of $5, 299 ± $1, 289 versus $10, 455 ± $2, 290 in the OR, P < 0.001. Total time of visit in the FRR was ∼30% less than the OR, P < 0.001. No notable delay in treatment was observed. Discussion: In the era of finite resources and value-based care, implementation of a FRR resulted in safe, cost-effective, and increased procedural efficiency.